Comparative genomics and transcriptomics depict ericoid mycorrhizal fungi as versatile saprotrophs and plant mutualists. Issue 3 (7th January 2018) - Martino, Elena; Morin, Emmanuelle; Grelet, Gwen‐Aëlle; Kuo, Alan; Kohler, Annegret; Daghino, Stefania; Barry, Kerrie W.; Cichocki, Nicolas; Clum, Alicia; Dockter, Rhyan B.; Hainaut, Matthieu; Kuo, Rita C.; et al.
Summary: Some soil fungi in the Leotiomycetes form ericoid mycorrhizal (ERM) symbioses with Ericaceae. In the harsh habitats in which they occur, ERM plant survival relies on nutrient mobilization from soil organic matter (SOM) by their fungal partners. The characterization of the fungal genetic machinery underpinning both the symbiotic lifestyle and SOM degradation is needed to understand ERM symbiosis functioning and evolution, and its impact on soil carbon (C) turnover. We sequenced the genomes of the ERM fungi Meliniomyces bicolor, M. variabilis, Oidiodendron maius and Rhizoscyphus ericae, and compared their gene repertoires with those of fungi with different lifestyles (ecto‐ and orchid mycorrhiza, endophytes, saprotrophs, pathogens). We also identified fungal transcripts induced in symbiosis. The ERM fungal gene contents for polysaccharide‐degrading enzymes, lipases, proteases and enzymes involved in secondary metabolism are closer to those of saprotrophs and pathogens than to those of ectomycorrhizal symbionts. The fungal genes most highly upregulated in symbiosis are those coding for fungal and plant cell wall‐degrading enzymes (CWDEs), lipases, proteases, transporters and mycorrhiza‐induced small secreted proteins (MiSSPs). The ERM fungal gene repertoire reveals a capacity for a dual saprotrophic and biotrophic lifestyle. This may reflect an incomplete transition from saprotrophy to the mycorrhizal habit, or a versatile life strategy similar to fungal endophytes. Abstract : See also the Commentary on this article bySelosse et al., 217 : 968–972 .